Statistical Modeling and Optimization of Laser Cladding Stellite 6/WC Composite Coating - Teng Wu; Wenqing Shi; Linyi Xie; Meimei Gong; Jiang Huang; Yuping Xie; Kuanfang He (Advances in Materials Science and Engineering)
A response surface was employed to establish a statistical model for influencing factors and response targets to study the influence of laser cladding process parameters on the quality of Co-based WC composite coating and reduce defects in the cladding layer. Analysis showed that the cladding step and laser power were the most significant factors affecting the coating’s porosity area and surface flatness. Increasing the amount of WC and the laser power significantly enhanced the hardness of the coating. The validation experiments under optimized conditions showed that the predicted value of the model was in good agreement with the actual value, and the average error was less than 6%. This study presents the preparation of Co-based WC ceramic composite coating by laser cladding and the optimization of process parameters.